الترجمة الآلية العصبية: بين الذكاء الاصطناعي والعقل البشري -تطبيق Deepl Translator أنموذجا-: Neural Machine Translation: Artificial Intelligence Versus the Human Mind - DeepL Translator Application as an Example - - boudraa , Mbarak; Makhloufi , zakaria (Maalim, 2024)
Translation is one of the most important traditional means of communication between peoples of different languages and cultural backgrounds, and an effective tool for achieving acquaintance and transferring knowledge and civilizations. With technological advances, the demand for machine translation that uses digital technology and artificial intelligence has increased more than ever. Moreover, neural machine translation, which uses complex artificial neural networks to simulate the human brain, is advanced because it outperforms human translation in terms of speed and the ability to store and retrieve information. This article attempts to explore the following research question: To what extent has neural machine translation, using DeepL Translator as a typical example, achieved the quality and accuracy of human translation?